Eksplorasi Teori Pembelajaran dan Implementasinya dalam Pendidikan Kontemporer - Miftahul Afkarina; Muhtar Hazawawi (Jurnal Ilmiah Profesi Pendidikan, 2025)
This study is a literature review using a descriptive qualitative approach to evaluate and compile data from various sources related to learning theories. The aim of the research is to describe the application of key learning theories, including behaviorism, cognitivism, constructivism, and humanism, in the context of education in Indonesia. The data sources include books, scholarly articles, and relevant previous research findings. The results of the study show that each learning theory offers a unique perspective on understanding the learning process. Behaviorism emphasizes behavioral change through stimulus-response relationships, while cognitivism focuses on the mental processes that support deep understanding. Constructivism prioritizes experiential learning and problem-solving, while humanism is oriented toward the holistic development of individual potential. The implementation of these theories in teaching, such as through group discussions, experiments, and personalized approaches, has proven to create a learning environment that supports students' cognitive, affective, and social development. Educators play a crucial role in the learning process, not only as information providers but also as facilitators who support students' intellectual, social, and emotional development. The teacher’s role as a source of learning, facilitator, manager, mentor, motivator, and evaluator significantly contributes to creating a conducive environment for effective learning. The success of learning is highly dependent on the teacher's skills in designing and managing the learning process to achieve educational goals optimally.